P78 Socio-economic Determinants of Colorectal Cancer Screening in Australia. (13th September 2016) - Jongcherdchootrakul, K; Flander, L; English, DR; Giles, GG; Jenkins, MA; Ouakrim, DA
Abstract : Background: Australia has the highest incidence of colorectal cancer (CRC) in the world. In 2010, 14, 860 new CRC cases diagnosed accounting for 12.7% of all new cancers. CRC is a complex disease and its aetiology, prevention and prognosis cannot be reduced solely to the analysis of people's individual and biological attributes. Research from the United State and Europe has consistently shown a close relationship between low socio-economic status (SES) and lower screening participation. While, it is of limited applicability and relevance to Australia given the specificities of its health system and the current state of its national bowel cancer screening program, which is being substantially under-utilised. The aim of this study is to provide contemporary Australian data on the association between CRC screening uptake and SES. Methods: We used data the Melbourne Collaborative Cohort Study (MCCS) to examine the relationship between colorectal cancer screening participation and SES variables (i.e. education level, country of birth and Index of Relative Socio-economic Disadvantage). We performed multivariate logistic regression analyses to estimate the association between Faecal Occult Blood Test (FOBT), sigmoidoscopy and colonoscopy screening and the SES variables of interest. We conducted both complete-case and multiple imputation analyses to estimate the effect of missing data on our findings. Results: 23, 027 MCCS participants with no previous colorectal cancer diagnoses were eligible for inclusion in this study. Prevalence of CRC screening with FOBT, sigmoidoscopy and colonoscopy was 13.1% (95% CI: 12.7–13.5), 8.8% (95% CI: 8.4–9.1) and 40.2% (95% CI: 39.6–40.8), respectively. Participants born overseas were less likely to screen with FOBT (OR: 0.50, 95% CI: 0.44–0.58), sigmoidoscopy (OR: 0.68, 95% CI: 0.58–0.80) and colonoscopy (OR: 0.79, 95% CI: 0.73–0.85) compared to those born in Australia. People living the less disadvantaged areas were more likely to screen with FOBT (OR: 1.17, 95% CI: 1.06–1.30) and colonoscopy (OR: 1.12, 95% CI: 1.04–1.20) compared to those in the most disadvantaged areas. Similarly, people with tertiary education had a greater likelihood of FOBT (OR: 1.21, 95% CI: 1.10–1.34) and sigmoidoscopy (OR: 1.25, 95% CI: 1.11–1.40) uptake compared with those who reached grade 10 or below. Conclusion: Our study shows that low socio-economic status is a strong predictor of poor compliance with colorectal cancer screening. This represents a major gap in the current CRC prevention policy in Australia. Our finding can inform future public health designed to reach the most disadvantaged segment of the population who are currently most likely to miss out on the benefits of regular CRC screening.